Kebijakan Kota Layak Anak Di Kabupaten Boyolali Dalam Upaya Pencegahan Tindak Pidana anak - Wibowo, Eko Ari; , Kuswardani SH., M.Hum; , Bambang Sukoco S.H.,M.H (2016)
Policies of Kota Layak Anak in Boyolali for crime Prevention of Children. Eko Ari Wibowo. C100110094. Faculty of Law. Muhammadiyah University of Surakarta. The research, entitled Policies of Kota Layak Anak in Boyolali for crime Prevention of Children. The purpose of this research is; To find out the policy of BP3AKB for create Kota Layak Anak in the district of Boyolali, to know the Implementation of Kota Layak Anak in the district of Boyolali, to know what the obstacles are often encountered in implementing by BP3AKB strugle of Kota Layak Anak progam in the district of Boyolali. BP3AKB policy in order to meet children's rights at the top Boyolali District Regulate foundation 14 Year 2013 regarding Child Protection. Implementasi Fulfillment of child rights held by PerMenNeg PP and PA No. 12 Year 2011 on indicators Regency/City Eligible Children, Law No. 35 Year 2014 on the Amendment of Act No. 23 of 2002 on Child Protection. Implementation of Children's Rights is implemented by carrying out cooperation between BP3AKB with SKPD who has authority in the fulfillment of child rights. Constraints the BP3AKB fight is commitment of employees that still need to be improved.